2004
DOI: 10.1111/j.1432-1033.2004.03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene encoding Lon protease from Brevibacillus thermoruber WR‐249 and biochemical characterization of its thermostable recombinant enzyme

Abstract: A gene encoding thermostable Lon protease from Brevibacillus thermoruber WR-249 was cloned and characterized. The Br. thermoruber Lon gene (Bt-lon) encodes an 88 kDa protein characterized by an N-terminal domain, a central ATPase domain which includes an SSD (sensor-and substrate-discrimination) domain, and a C-terminal protease domain. The Bt-lon is a heat-inducible gene and may be controlled under a putative Bacillus subtilis r A -dependent promoter, but in the absence of CIRCE (controlling inverted repeat o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 68 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…The critical requirement for ATP in our Lon-1 chaperone assay results is in agreement with that reported for chaperones in general [64] and for yeast Lon [58],[60], but differs with one study in which the chaperone-like activity of a bacterial Lon was investigated. In that report, Lon from Brevibacillus thermoruber prevented insulin aggregation in an ATP-independent manner [59].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The critical requirement for ATP in our Lon-1 chaperone assay results is in agreement with that reported for chaperones in general [64] and for yeast Lon [58],[60], but differs with one study in which the chaperone-like activity of a bacterial Lon was investigated. In that report, Lon from Brevibacillus thermoruber prevented insulin aggregation in an ATP-independent manner [59].…”
Section: Resultsmentioning
confidence: 90%
“…In addition to its function as an ATP-dependent protease, Lon exhibits a chaperone-like role in mammalian mitochondria, yeast, and bacteria [58],[59],[60],[61],[62]. Cloud et al [28] reported that complementation of an E. coli lpxA temperature-sensitive mutant with sequence corresponding to the N-terminus and ATP-binding site of B. burgdorferi lon-1 allowed the mutant to grow at the non-permissive temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of enzyme-DNA complexes was monitored by a deceleration of DNA in an agarose gel (GMSA method) [21]. 20–25 μg of Lon-H 6 or Lon-dHI(CC) were incubated for 30 min at 25°C with 500 ng of plasmid DNA (pET28a) in 25 μL of 20 mM Tris-HCl buffer, pH 7.5, containing 60 mM NaCl.…”
Section: Dna Purificationmentioning
confidence: 99%
“…Wang et al (2012) reported about a Brevibacillus species that produced thermostable protease with slightly different characters to the one produced by strain LII (optimum temperature 75 °C and optimum pH 9). Another experiment on this bacteria was reported by Lee et al (2004). Lee's group reported the presence of a its ability to degrade fibroin which is one of the substrates of protease (Suzuki et al 2009).…”
Section: Short Communicationmentioning
confidence: 99%